UNVEILING STIGMA: EXPLORING THE DETRIMENTAL EFFECTS OF YEMENI-ARABIC PROVERBS AND SAYINGS ON INDIVIDUALS WITH DISABILITY - Mohammed Hejash; Abdulaziz Ahmed (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
This study investigates the stereotypical representations and psychological implications of Yemeni-Arabic proverbial language that describes persons with disabilities, examining how such expressions become normalized as tools of “wisdom” in everyday discourse. While Classical and Modern Standard Arabic possess a rich lexicon for praising perfection, many vernacular proverbs and sayings associate physical, mental, and sensory impairments with imperfection. Adopting a qualitative approach based on cognitive semantic analysis, the study examines a corpus of 71 Yemeni proverbs collected from publicly available compilations, with a detailed analysis of 15 representative examples. The analysis demonstrates how disability is metaphorically employed to signify weakness, incompetence, misfortune, or irrationality, reflecting deeply rooted cultural conceptualizations. Through repeated use, these expressions are normalized as embodiments of collective wisdom, rendering their stigmatizing meanings socially acceptable and often invisible. However, growing sociolinguistic awareness and the promotion of inclusive language challenge the assumed wisdom of such expressions by emphasizing that no inherent connection exists between disability and imperfection. While many individuals with disabilities actively contribute to their communities, stigmatizing proverbial language may still produce psychological harm and reinforce negative social attitudes. The study highlights the need for greater linguistic awareness in Yemeni society and calls for critical reflection on everyday expressions that shape perceptions of disability and influence social inclusion.